Blade runner 2019. 3, Home again, home again - Johnson, Mike (Comic book author) (Titan Comics, 2021)
"Los Angeles, 2026. Ex Blade Runner Aahna 'Ash' Ashina returns to Los Angeles to settle the score with agribusiness tycoon Alexander Selwyn who had sold his daughter, Cleo, to Eldon Tyrell for genetic experimentation. In a city still suffering from the effects of the Black Out, Ash -- once the huntress -- is now the hunted, as the LAPD, the underworld, and a rogue group of Replicants search the city looking for her. With no friends and a price on her head, nowhere is safe for Ash. She is forced to turn for help from an unlikely source as she searches for a lead to Selwyn and a bloody reckoning..."--Provided by publisher.